LEGAL CERTAINTY OF ECONOMIC RIGHTS FOR UNREGISTERED CREATORS IN COLLECTIVE MANAGEMENT ORGANIZATIONS - Adri Putra, Anak Agung Bagus Jaya; Dananjaya, Nyoman Satyayudha (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This writing aims to analyze, identify, and elaborate on the legal protection of the economic rights of copyrighted works in Indonesia, based on the UUHC (Undang-Undang Hak Cipta or Copyright Law), and the legal certainty of economic rights for creators who are not registered with the Collective Management Institute after the enactment of PP (Peraturan Pemerintah or Government Regulation) Number 56 of 2021 concerning the Management of Copyright and/or Music Royalties. This study employs normative research with a statutory approach and analysis of legal concepts. The results indicate that the protection of creators' economic rights under the UUHC is regulated by Article 9, paragraph 3, which states that "any person without the permission of the creator or copyright holder is prohibited from copying and/or commercial use of the work." Copyright infringement will result in the perpetrator being classified as committing a criminal act in accordance with Article 113, paragraphs (1), (2), (3), and (4) of the UUHC. Additionally, repressive protection can be pursued through litigation and non-litigation means. To address the decarbonization related to exclusive rights between the UUHC and PP No. 56 of 2021, the resolution involves vertical harmonization, which requires the alignment of one law with the provisions of other laws and regulations that occupy different hierarchical positions.